Sistem Boarding School dalam Meningkatkan Pembinaan Akhlak di Pondok Pesantren Hasan Al-Massyath Nahdatul Wathon Gunung Sesang Terara: The Boarding School System in Improving Moral Development at the Hasan Al-Massyath Nahdatul Wathon Gunung Sesang Terara Islamic Boarding School - Syahdan; Sirajun Nasihin; Fitri Aulia (Pendidikan Al-Gafari, 2025)
Islamic boarding schools (Pondok Pesantren) are a type of Islamic educational institution that is unique to Indonesia. The term